CLINICAL PROFILE AND ETIOLOGICAL EVALUATION OF NON-TRAUMATIC MYELOPATHIES USING MAGNETIC RESONANCE IMAGING - BEHERA, BIJAYA KUMAR; JENA, SUKANTA KUMAR; BEHERA, NISARG (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The present study was conducted with an objective to identify the etiology of non-traumatic myelopathies of both compressive and non-compressive types with the aid of magnetic resonance imaging (MRI). Methods: This retrospective observational cross-sectional study was conducted on 100 patients with a clinical diagnosis of non-traumatic myelopathy belonging to the age group of 15–75 years from August 2018 to July 2020 in the Departments of General Medicine and Radiodiagnosis of MKCG Medical College and Hospital, Berhampur, Odisha. Detailed history, clinical evaluation, laboratory investigations, and findings of MRI spine and brain were compiled. Results were analyzed using descriptive statistics. Results: Among 100 patients of non-traumatic myelopathy, 65 patients presented with compressive myelopathy and 35 patients with non-compressive myelopathy where 56 patients presented with paraparesis and 44 with quadriparesis. Pott’s spine (n=25, 38.46%) and acute transverse myelitis (ATM) (n=24, 68.57%) were the most common etiologies found in compressive and non-compressive groups, respectively. Conclusion: Pott’s Spine, spondylotic myelopathy, and ATM were the most common etiologies of non-traumatic myelopathy. MRI has proven to be the ultimate imaging modality for their etiological evaluation.